Is essential tremor a Purkinjopathy? The role of the cerebellar cortex in its pathogenesis. Issue 13 (30th September 2013) - Grimaldi, Giuliana; Manto, Mario
ABSTRACT: Essential tremor (ET) encompasses a group of progressive neurological diseases in which the primary clinical feature is kinetic tremor of the arms. There is accumulating evidence to suggest that the cerebellum is involved in the pathogenesis of ET; the clinical presentation, neurophysiological data, and functional and metabolic abnormalities revealed by neuroimaging studies all point toward the dysregulation of cerebellar circuits. Recent neuropathological findings at postmortem demonstrate that Purkinje neurons, and some brainstem neurons, play an integral role in the pathogenesis of this common neurological disorder. The assessment of Purkinje cell linear density shows that Purkinje density is abnormal in ET brains. Specific efforts need be devoted to understanding the molecular and cellular events occurring in the Purkinje neurons of the cerebellar cortex, which are emerging as being of particular importance in the pathogenesis of ET in a subgroup of patients. © 2013 International Parkinson and Movement Disorder Society.